Responses of hydrodynamics to changes in shoreline and bathymetry in the Pearl River Estuary, China - Lin, Shicheng; Liu, Guangping; Niu, Jianwei; Wei, Xing; Cai, Shuqun (Continental shelf research, 2021)
Numerous estuaries worldwide have been modified in the past decades by human interventions. The shoreline and bathymetry in the Pearl River Estuary (PRE) have changed greatly over the past 40 years due to the influence of land reclamation and waterway dredging, which have resulted in the corresponding adjustment of its hydrodynamics. Utilizing the ROMS numerical model, this paper studies the hydrodynamic responses to changes in shoreline and bathymetry in the PRE from 1971 to 2012. The results show that, on one hand, during neap tide, the change in the shoreline makes the residual current in the West Channel (WC) increase by 0.10 (0.05) m/s at maximum in the surface (near bottom) layer. Therefore, the exchange flow increases by 9.5% and the longitudinal circulation strengthens. The surface isohalines move southward up to 18 km, but the bottom isohalines move northward ∼2 km in the WC and East Channel (EC), which is different from the previous conclusion that the seaward extension of coastlines inhibits saltwater intrusion. The decrease in salinity in the upper layer reduces the upper seaward salt transport, resulting in a larger net landward salt transport from 25.21 × 103 kg/s to 35.44 × 103 kg/s. During spring tide, the changes are relatively weaker, but the direction of salt transport changes to seaward and the net seaward transport also increases. Moreover, the change in shoreline reduces the water area and volume in the PRE by 21.3% and 15.6% respectively, which causes a reduction of 11.3% (17.1%) in tidal prism during spring (neap) tide. The wave celerity is enhanced (>23%) and the amplification of semidiurnal tide is strengthened (>20%) in the WC and West Shoal (WS). The reduction in tidal prism together with the strengthened reflection of tidal waves with a larger phase lag between elevation and velocity of M2 tidal component cause a significant decrease of 19.0% in tidal energy flux entering the PRE. However, the tidal range increases by ∼0.30 m (mainly due to the increase in M2 tidal amplitude) in the EC, which is induced by lower tidal energy dissipation there. On the other hand, during neap tide, the change in bathymetry greatly enhances the bottom landward residual current whose peak value increases by 80% in the WC, thereby increasing approximately 14 km of the intrusion distance of saline water, enhancing the exchange flow by 27.5% and strengthening the longitudinal circulation. The net landward salt transport increases to 38.39 × 103 kg/s. The results during spring tide are similar to those during neap tide but with smaller changes, and the net seaward salt transport decreases. Moreover, the wave celerity is slightly reduced (<8%) and the amplification of semidiurnal tide is also decreased (<10%) in the WC and WS. Meanwhile, the change in bathymetry only decreases the water volume by 4.7%, leading to a relatively smaller effect on the tidal prism, and it strengthens (weakens) the reflection of tidal waves in the West Shoal and Middle Shoal (WC and EC), resulting in a slight reduction in tidal energy flux entering the bay. In the WC, the tidal range is basically unchanged since the increased tidal energy flux is offset by the increased dissipation. The quantitative results obtained in this study may provide some references for the development and protection of the PRE and other estuaries that are subject to strong human interventions. •Seaward extension of coastlines increases tidal range, wave celerity and saltwater intrusion.•Change in bathymetry increases ∼14 km of the intrusion distance of saltwater.•Change in bathymetry enhances exchange flow by 27.5%, reduces tidal energy flux by 2.4%.